Flexible Activities of the Organization in Implementation of the Sustainable Development Principles in Selected Areas of the Organizations - Lemańska-Majdzik, Anna (European Journal of Sustainable Development, 2018)
Flexible activities of the organization result from changes in the market environment. However, the multidimensionality of the concept of flexibility of actions leads to considerations in the field of organizational behavior from the perspective of business management. The aim of the paper is to compare flexible activities of companies in the implementation of sustainable development principles in selected areas of ongoing activities. The research in the form of case study was conducted at the turn of 2017 and 2018 on the basis of the interview questionnaire. The inference is based on the results of own research on selected organizations: profit and nonprofit, which declared the implementation of sustainable development principles in their current operations. The conducted research allowed to compare the activities aimed at introducing the above-mentioned principles in the selected areas of organiations' activities. Since the main objectives of the organizations' activities are assumed to be different, the desire to implement the principles of sustainable development may result not only from the main goals of the company, but also from changes in the business environment, customer expectations and from sustainable development-oriented leadership. Keywords: Flexibility activities, principles of sustainable development, business management, profit and nonprofit organizations